Summer on campus - learning robotics with fun - Ribeiro, A. Fernando (2010)
After the academic year, summer comes and students spend some time at home without anything to do. It is time to rest but summer is long. In order to prepare youngsters for the future, the University of Minho organizes short courses (one week long) called “Summer on Campus”, on which students can work on the university laboratories, feeling the excitement of working in such places, tutored by a Professor, in small groups of 10-20 people. On these courses, they spent the mornings on the labs and the afternoons on cultural or sportive activities. They meet new friends, they learn new things and they have some fun at a University. One of those courses is called “Robotics for Juniors – come and build your own” and teaches how to build a robot.. In this course the students are first introduced to the most basic electronics components, then they are taught the basics for programming. They are given a robotic Kit Bot’n Roll which they have to assemble, soldering the electronic components, program it and they participate on small contests with the robots. The experience is well appreciated by all. This paper described this robotics course in detail and the results obtained.